PROTECTIVE EFFECT OF NEWBOULDIA LAEVIS LEAF EXTRACT AGAINST DYSLIPIDEMIA AND HEPATORENAL DYSFUNCTION IN DIABETIC RATS - KOLAWOLE O. TIMOTHY,; AKANJI M. ADEWUMI, (International Journal of Pharma and Bio Sciences, 2014)
Diabetes mellitus has become a global health problem and its prevalence is increasing at an alarming rate. Management of diabetes and its complications with drugs that are easily accessible and have minimal side effects remains a serious challenge among medical scientists. In this study, we investigated the effects of ethanol extract of the leaves of Newbouldia laevis on dyslipidemia and hepatorenal dysfunction in diabetic rats. Experimental diabetes was induced in rats by intravenous injection of streptozotocin. Diabetic rats were then treated with graded doses of Newbouldia laevis extract for 28 days. Serum analysis showed that there was significant reduction in the serum levels of aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, creatinine and urea in extract-treated rats. Serum levels of total cholesterol, triglycerides and low density lipoprotein cholesterol were significantly reduced while serum level of high density lipoprotein cholesterol was raised. The results of this study suggest that extract of the leaves of Newbouldia laevis could protect diabetic rats against dyslipidemia and hepatorenal dysfunction.